Efektivitas Dan Efisiensi Anggaran Pendapatan Dan Belanja Desa Di Desa Koyobunga: Effectiveness and Efficiency of Village Revenue and Expenditure Budget in Koyobunga Village - Alfrevaldo Bae Bae; Yofandi Djibran Himran (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2019)
This study aims to determine the Effectiveness and Efficiency of the Village Revenue and Expenditure Budget in Koyobunga Village. The benefits of this research are as information material for the Koyobunga village government in managing the Village Revenue and Expenditure Budget. The analytical tool used is the ratio of effectiveness and efficiency, namely analyzing target data, expenditure realization, and income using the ratio of effectiveness and efficiency. The effectiveness ratio describes the ability of the Koyobunga Village government to realize the Village Revenue and Expenditure Budget to carry out the planned program compared to the target that has been set based on the real value potential. The efficiency ratio is the ratio between the costs incurred for the expenditure of Koyobunga village government activities to obtain certain income, while the data used is secondary data. The results of this study indicate that the average value of the effectiveness of the management of the Village Budget in Koyobunga Village is 93% which meets the effective criteria, with the highest percentage level in 2015 being 99% (effective) and the lowest percentage level in 2017 being 82 % (effective enough). Meanwhile, the average efficiency level is 83% in the fairly efficient category, with the lowest efficiency level in 2017 being 75% (efficient) and the highest in 2019 being 94% (less efficient).